2009
DOI: 10.1016/j.jvs.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience and outcome of a new hemodialysis access device for catheter-dependent patients

Abstract: In access-challenged patients, a statistically significant reduction in HeRO-related bacteremia was noted compared with TDC literature. The device had similar function and patency compared with conventional arteriovenous graft literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
2
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 33 publications
7
88
2
5
Order By: Relevance
“…The number of interventions required to maintain the HeRO are similar to other series of secondary access particularly in this especially complex population. 5 Further international studies are necessary to report the experience of the HeRO graft in non-US populations and multicentre randomized controlled trials to compare the graft with catheters or alternative access procedures in such complex access problems.…”
Section: Resultsmentioning
confidence: 99%
“…The number of interventions required to maintain the HeRO are similar to other series of secondary access particularly in this especially complex population. 5 Further international studies are necessary to report the experience of the HeRO graft in non-US populations and multicentre randomized controlled trials to compare the graft with catheters or alternative access procedures in such complex access problems.…”
Section: Resultsmentioning
confidence: 99%
“…A satisfactorily low incidence of bacteremia was reported at 0.7/1,000 days for a HeRO alone compared with 5.1/1,000 days if a bridging catheter was required. 19 Katzman et al 20 reported the results of 36 patients with HeRO grafts and noted an 8-month primary patency of 38.9% and secondary patency of 72.2%. In our practice, a patient able to have either a CWAVG or a HeRO usually receives a CWAVG first.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Hemodialysis Reliable Outflow (HeRO) grafts (CryoLife, Inc., Kennesaw, GA) are designed to bypass preexisting central venous stenosis by connecting the brachial artery with the venous circulation through the ipsilateral internal jugular vein (IJV) (figure, C and D). 3 We report a case of intracranial hypertension immediately after placement of a HeRO graft, review similar cases in the medical literature, and discuss possible pathophysiology.…”
mentioning
confidence: 92%